Development of Video Based Economics Learning Media for Vocational High Schools: Pengembangan Media Pembelajaran Ekonomi Berbasis Video untuk Sekolah Menengah Kejuruan - Finia Zelyana Astri; Agus Wahyudi (Institute of Educational, Research, and Community Service, 2023)
This study aims to develop video-based learning media that aligns with the Economics curriculum for Vocational High Schools. This research was conducted at Darul Wustho Jerowaru Vocational High School. Effective and engaging learning media can enhance students' interest in and understanding of economic subjects. This research follows a research and development approach, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Based on the research findings, the assessment of the content aspect by two content experts yielded an average total score of 3.45, indicating a highly suitable category. The assessment by the media expert indicated that the media engineering aspect received an average score of 3.3, falling within the highly suitable category. The visual communication aspect received an average score of 3.27, also classified as highly suitable. The instructional design aspect obtained an average score of 3.26, which falls under the highly suitable category. Overall, the evaluation of the media's suitability for learning by the media expert resulted in an average total score of 3.27, indicating a highly suitable category. Consequently, it can be concluded that the development of video-based learning media for economics is considered suitable for implementation in vocational high school economics education